Pengaruh Beberapa Umpan Pendahuluan Terhadap Jumlah Umpan Beracun Yang Dimakan Tikus Sawah - Yusna Maulida Putri; Akhmad Gazali; Antar Sofyan (Agroekotek View, 2021)
The ability of rats to make them an important pest in agriculture, rats start attacking the rice nursery phase until the storage of crops in the warehouse. Several methods of controlling rats that have been used include sanitation methods, technical culture methods, physical methods, mechanical methods, biological methods and chemical methods. The control methods most often used by farmers are mechanical methods using traps and chemical methods. Chemical methods using poison bait have shown to be killing power and are effective in killing real mice, pre-bait is used to make it easier for mice to eat the poisonous bait given. This research was conducted to determine the effect of several pre-feeds on the amount of poisonous bait eaten by field mice and the type of pre-bait mostly eaten by field rats. The research was carried out in the farmers' rice fields of Banua Budi Village, Kab. Hulu Sungai Tengah Prov. South Kalimantan using a completely randomized design (CRD) with one factor, namely the difference in the effect of the five types of preliminary bait to lure rats to eat poisonous bait which is repeated four times. The results showed that pre-feeding had a significant effect on the amount of poisonous bait eaten by field mice and the type of pre-bait that was mostly eaten by rats was P2 (Boiled Instant Noodle) treatment.